2011
DOI: 10.1002/ijc.26274
|View full text |Cite
|
Sign up to set email alerts
|

Urinary acylcarnitines are altered in human kidney cancer

Abstract: Kidney cancer often diagnosed at late stages when treatment options are severely limited. Thus, greater understanding of tumor metabolism leading ultimately to novel approaches to diagnosis are needed. Our laboratory has been utilizing metabolomics to evaluate compounds appearing in kidney cancer patients’ biofluids at concentrations different from control patients. Here, we collected urine samples from kidney cancer patients and analyzed them by chromatography coupled to mass spectrometry. Once normalized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 28 publications
8
89
0
Order By: Relevance
“…Metabolomic profiling was performed as described previously for the analysis of saliva, plasma, and urine [19][20][21]. For all matrices, samples from the three consumer groups were extracted and split into equal parts for analysis on gas chromatography/mass spectrometry and liquid chromatography/mass spectrometry/mass spectrometry platforms [22].…”
Section: Metabolomic Profiling Technologymentioning
confidence: 99%
“…Metabolomic profiling was performed as described previously for the analysis of saliva, plasma, and urine [19][20][21]. For all matrices, samples from the three consumer groups were extracted and split into equal parts for analysis on gas chromatography/mass spectrometry and liquid chromatography/mass spectrometry/mass spectrometry platforms [22].…”
Section: Metabolomic Profiling Technologymentioning
confidence: 99%
“…3 To this day, we use targeted metabolomics whenever we use a urinary dipstick at the bedside or clinical laboratory. More recently, yet prior to its current appellation, metabolomics-type evaluations of both plasma cancer grade, with most acylcarnitines being increased in the urine of cancer patients and in those patients with high cancer grades, 18 suggesting involvement of fatty acid oxidation in RCC energy metabolism. In addition to biomarker studies, a human RCC to mouse xenograft metabolomics study of urine, blood, and malignant tissues resulted in identification of several novel therapeutic targets by showing that there exists alteration of metabolites in tryptophan, peroxisome proliferator-activated receptor α (PPARα), and fatty acid oxidation pathways; 17 these targets are currently being validated in our laboratory with initially promising results.…”
Section: Techniques Of Metabolomics Analysismentioning
confidence: 99%
“…Urine analysis in individuals with RCC identified quinolinate, 4-hydroxybenzoate, and gentisate, which are involved in pathways of amino acid and energetic metabolism, consistent with cancers exhibiting a Warburg phenotype (79). The detection of acylcarnitines in the urine during a separate study suggested a biomarker of advanced RCC (47). The role of NOX oxidases, upstream or downstream, of cancer metabolism has not been studied, but it is an active area of investigation in our laboratory.…”
Section: Metabolomicsmentioning
confidence: 94%